2021
DOI: 10.1186/s12864-021-07989-1
|View full text |Cite
|
Sign up to set email alerts
|

Global identification of long non-coding RNAs involved in the induction of spinach flowering

Abstract: Background Spinach is a beneficial annual vegetable species and sensitive to the bolting or early flowering, which causes a large reduction in quality and productivity. Indeed, bolting is an event induced by the coordinated effects of various environmental factors and endogenous genetic components. Although some key flowering responsive genes have been identified in spinach, non-coding RNA molecules like long non-coding RNAs (lncRNAs) were not investigated yet. Herein, we used bioinformatic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…Samples from 5 different seedlings were pooled together as one biological sample. Three biological replicates from each genotype were used for RNA extraction and the Real-Time PCR (qPCR) analysis according to the previous research [ 11 , 131 , 132 ]. In brief, total RNAs were extracted by the DENAzist column RNA isolation kit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples from 5 different seedlings were pooled together as one biological sample. Three biological replicates from each genotype were used for RNA extraction and the Real-Time PCR (qPCR) analysis according to the previous research [ 11 , 131 , 132 ]. In brief, total RNAs were extracted by the DENAzist column RNA isolation kit.…”
Section: Methodsmentioning
confidence: 99%
“…What is still slightly ambiguous, is the putative roles of non-coding genes. Transcripts of non-coding genes have revealed regulatory functions in different pathways affecting flowering and the reproductive switch [ 11 ]. One of these types of transcripts is the long non-coding RNA known as lncRNA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, reports on the plant lncRNAs have demonstrated they act as key regulatory elements in nearly all developmental process, including root organogenesis (Ganguly et al, 2021), flowering time (Heo and Sung 2011;Ghorbani et al, 2021), photo morphogenesis (Wang et al, 2014), and reproduction (Zhang et al, 2014;Fang et al, 2019). The studies reported plant lncRNAs with diverse biological mechanisms played in developmental process, biotic and abiotic stress responses (Swiezewski et al, 2009;Heo and Sung, 2011;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%